ANALISIS KEUNTUNGAN USAHA TERNAK BABI DI KECAMATAN TOMOHON BARAT KOTA TOMOHON (Studi Kasus Pada Usaha Milik Bapak Okny Mende) - Anes, Candy A.A; Massie, M T; Lumy, T F.D; Sajow, A A; Oroh, F N,.S (Universitas Sam Ratulangi, 2020)
PROFIT ANALYSIS OF PIG FARMING IN WEST TOMOHON DISTRICT TOMOHON CITY. (Case Study On Mr. Okny Mende's Business. The goal of this study was to investigate profit of pig farming in West Tomohon District Survey method was performed on Mr Okny Mende’s farming in Tara Tara 2 Village West Tomohon District bycase study. The pig farmers’ challenge in the production process was the high cost of production. The increase of cost production without profit tend to be problem for farmers because input material (production costs) was very important factors in the livestock business. The Pig farming business has the potential for development in the City of Tomohon due to investment in this business does not require large costs and land, besides that the return on capital is relatively faster and although the development of pig agribusiness is limited due to socio-cultural factors, but in North Sulawesi especially Tomohon City has good prospects because of high demand of local market and the surrounding area, and there are no socio-cultural constraints. The pig farm business located in Taratara Dua Sub-District, West Tomohon District is owned by Mr. Okny Mende's family, which is a nursery business by selling weaned piglets. Results of this study shown that the average total cost incurred per period of production as much as IDR 38.334.531. While revenue per period of production was IDR. 68.400.000. The profit per production period was IDR. 30.065.469.